2016
DOI: 10.1074/jbc.m115.704064
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Human DNA Primase Interaction with Template-Primer

Abstract: DNA replication in almost all organisms depends on the activity of DNA primase, a DNA-dependent RNA polymerase that synthesizes short RNA primers of defined size for DNA polymerases. Eukaryotic and archaeal primases are heterodimers consisting of small catalytic and large accessory subunits, both of which are necessary for the activity. The mode of interaction of primase subunits with substrates during the various steps of primer synthesis that results in the counting of primer length is not clear. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 46 publications
4
104
3
Order By: Relevance
“…Furthermore, the electrostatic interactions are extended by the DNA backbone of the DNA/RNA duplex. This structure explains why the elimination of 5Ј-triphosphate and/or 3Ј-overhang abolished the interaction of DNA/RNA with p58 C as well as with fulllength primase in our recent study (26).…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…Furthermore, the electrostatic interactions are extended by the DNA backbone of the DNA/RNA duplex. This structure explains why the elimination of 5Ј-triphosphate and/or 3Ј-overhang abolished the interaction of DNA/RNA with p58 C as well as with fulllength primase in our recent study (26).…”
Section: Resultssupporting
confidence: 53%
“…However, the mechanism of switch and involved domains remained unknown. Recently we found that p58 C makes a tight complex with a 7-bp DNA/RNA duplex with almost the same affinity for the template/primer as a whole primase (26). Moreover, the final and intermediate products of primase reaction have similar affinity for primase (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations